Early Childhood Physical Motor Development - Al Ihzan Tajuddin; Ronald Dwi Ardian Fufu; Salmon Runesi (Early Childhood Education Development and Studies (ECEDS), 2022)
Motor development is one aspect that must be considered in its development in early childhood. Motor development is often used as a benchmark to prove that children are growing and developing well. Motor development is something that talks about coordinated physical movements, so that in its development it takes a variety of appropriate stimulation for early childhood. Motor development is one of the most important factors in the development of the individual as a whole. Basically, this development develops in line with the maturity of the nerves and muscles of the child. Thus, every movement, no matter how simple, is the result of a complex interaction pattern of various parts of the system in the body that is controlled by the brain. The results of this study indicate that children who have good physical-motor development, when children are able to coordinate their body muscle movements optimally. Conducive environment, parenting patterns, nutritious food are factors that support children's physical-motor development, especially when they are still under the age of five (toddlers).